Attendance policies, instructor communication, student attendance, and learning. Issue 2 (17th February 2016) - Snyder, Jason; Frank, Lisa A. C.
ABSTRACT: The authors utilized a quasiexperimental design across five sections of a managerial communication course ( N = 150) to test the role of course policies and student perceptions of the instructor in influencing student absenteeism and three indicators of student learning: grades, affective learning, and cognitive learning. The experimental group received a class attendance policy containing a grade-related contingency. Results suggest that the three indicators of student learning are associated with different predictors. Moreover, the appropriate attendance policy sets the stage for learning.